2022
DOI: 10.1088/1742-6596/2244/1/012009
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of ionization, charge exchange and ion confinement times in charge breeder ECR ion sources with short pulse 1+ injection of metal ions

Abstract: The Consecutive Transients (CT) method is used for estimating the characteristic times of ionization, charge exchange and confinement within the plasma of a Charge Breeder Electron Cyclotron Resonance Ion Source (CB-ECRIS). The method reveals differences in the characteristic times between different source configurations, with K9+ charge breeding efficiencies of 8.9 % and 20.4 %, and allows qualitative explanation of the improved breeding efficiency. The increase in K9+ efficiency is accompanied by a decrease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…We have recently developed a method which satisfies these conditions. The so-called consecutive transients (CT) method [15,16] for estimating the ECR-heated plasma properties, i.e., the electron density, average energy of the EED, characteristic times of ionization, charge exchange, and ion confinement. It is based on causing a small perturbation and monitoring the response of the complex system to it, requiring fewer a priori assumptions than any previous method and, uniquely, accounts for the experimental uncertainty of the electronimpact ionization cross sections employed in the calculations involved in this and similar methods [17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…We have recently developed a method which satisfies these conditions. The so-called consecutive transients (CT) method [15,16] for estimating the ECR-heated plasma properties, i.e., the electron density, average energy of the EED, characteristic times of ionization, charge exchange, and ion confinement. It is based on causing a small perturbation and monitoring the response of the complex system to it, requiring fewer a priori assumptions than any previous method and, uniquely, accounts for the experimental uncertainty of the electronimpact ionization cross sections employed in the calculations involved in this and similar methods [17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…The consecutive Transient (CT) method [18,19] is a recently developed method combining computational techniques and experiments for probing the plasma density n e , (warm) electron average energy ⟨E e ⟩, and characteristic times of ion confinement τ conf , charge exchange τ cex and electron impact ionization τ ion in CB-ECRIS plasmas. The CT method is based on short pulse 1+ injection into the ECRIS plasma and the analysis of the resulting N+ ion beam transients extracted from the ECRIS.…”
Section: Introductionmentioning
confidence: 99%
“…As such, the method either complements existing CB-ECRIS diagnostics while requiring fewer assumptions, or provides information inaccessible through other techniques. For example, it has been shown with the CT method that the ion confinement time is not a linear function but rather increases exponentially with the charge state [18,19], which is commensurate with electrostatic ion confinement in a local potential dip [5,6]. It has been shown that the inherent uncertainties of the CT method can be reduced e.g.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations